Hip structure associated with hip fracture in women data from the Geelong Osteoporosis Study (GOS) - Najmah; Gurri, L; Henr, M; Pasco, J (Universiti Kebangsaan Malaysia, 2011)
Aging leads to changes in bones to be highly fragile causing fractures. In this research, changes in the dimensions of the hip structure can be measured by using a computer program called ‘Hip Structural Analysis (HSA)’. The objective of this study is to estimate the association between hip geometries in Femoral Neck (FN) and the risk of hip fracture in older women.A case control study was performed to explore the objective respectively using the data of participants from population cohort and fracture cohort of the Geelong Osteoporosis Cohort Geelong, Southern Victoria, Australia. Simple and multiple logistic regressions were performed.Of total of 598, comparing Fracture group (44 subjects) and nonfracture group (454 subjects) aged over 63 years, the odds of hip fracture increased by approximately 2 fold for each 1 SD increase in width (OR=1.70(1.18-2.45,p 0.005), endocortical diameter (OR=1.80 (1,23-2.62, p=0.002), and buckling ratio (OR=1.85(1.32- 2.61, p < 0.0001) and for each 1 SD decrease in BMD (OR=1.98(1.21-3.23, p.0.006) and average cortical thickness (OR=2.02(1.23-3.34), p.0.006) controlling for age, height, weight and menopausal status. Findings suggest that not only is BMD associated with hip fractures, but also other hip geometry dimensions, including WID, ENDO, AVCO and AVBR, independent of age, height, weight and physical activity.These results provide additional insights that the geometries of FN is associated with fracture neck of femur in older women and strongly suggest its potential value, not only BMD, as clinical predictors for assessing the risk of hip fracture in older women. In addition to this, utilization of some combined parameters of bone geometries in FN might be a more effective method in screening than case findings to reduce the burden of hip fracture in the future. Further statistical methods is needed to analyze the combined hip structure to predict hip fracture